An individually randomized controlled trial to determine the effectiveness of the Women for Women International Programme in reducing intimate partner violence and strengthening livelihoods amongst women in Afghanistan: trial design, methods and baseline findings - Andrew Gibbs; Julienne Corboz; Mohammed Shafiq; Frozan Marofi; Anna Mecagni; Carron Mann; Fazal Karim; Esnat Chirwa; Charlotte Maxwell-Jones; Rachel Jewkes (BMC, 2018)
Abstract Background Intimate Partner Violence (IPV) is the most common form of violence in conflict and post-conflict settings, but there are few evaluations of interventions to prevent IPV in such settings. Methods The Women for Women International (WfWI) intervention is a year-long combined economic and social empowerment intervention for marginalized women survivors of conflict. Primarily, it seeks to support women to achieve four key outcomes: women earn and save money; women improve their health and well-being; women influence decisions in their homes and communities; women connect to networks for support. The organization recognizes Violence Against Women and Girls (VAWG) as a significant barrier to women's empowerment and expects to see reduction in VAWG, and specifically IPV, as part of building women's social and economic empowerment. This program is being quantitatively evaluated through an individually randomized control trial amongst women in Afghanistan, with a 24-month follow up. A comparison of baseline characteristics of participants is also included as well as a discussion of implementation of the baseline research. Discussion There is a high demand amongst Afghan women for such interventions, and this posed challenges in completing the randomization and baseline. In addition, the complex security situation in Afghanistan also posed challenges. However, despite these issues, recruitment was successfully achieved and the arms were balanced on socio-demographic measures. The evaluation will contribute to the limited evidence base on interventions to prevent IPV in conflict-affected settings. Trial registration NCT03236948 . Registered 28 July 2017, retrospectively registered.